The Burden of Respiratory Viruses and Their Prevalence in Different Geographical Regions of India: 1970–2020 - Waghmode, Rushabh; Jadhav, Sushama; Nema, Vijay (Frontiers in Microbiology, 2021)
As per the national health portal of India’s report of 2019, 41,996,260 cases and 3740 deaths from respiratory infections were recorded across India in 2018. India contributes to 18% of the global population with Severe Acute Respiratory Infection (SARI) as one of the prominent causes of mortality in children below 05 years. Measures in terms of diagnosis and surveillance of respiratory infections are taken up globally to find their circulating types, detect outbreaks and estimate disease burden. Similarly, the purpose of this review was to determine the prevalence of respiratory infections in various regions of India through published reports. Understanding the pattern and prevalence of various viral entities responsible for infections and outbreaks can help designing better strategies to combat this problem. The associated pathogens comprise Respiratory syncytial virus, Rhinovirus, influenza virus, Parainfluenza virus, Adenovirus, etc. Identification of these respiratory viruses was not given high priority till now but the pandemic of SARS-CoV-2 has sensitized our system to be alert about the burden of existing infections and to have proper checks for emerging ones. Most of the studies reported to date have worked on the Influenza virus as a priority. However, the data describing the prevalence of other respiratory viruses with their seasonal pattern has significant epidemiological value. A comprehensive literature search was done to gather the data from all geographical regions of India comprising of all states of India from 1970 to 2020 and the same has been compared with the global scenario and is being presented here.